Detection of antibodies to Ehrlichia spp. in dromedary camels and co-grazing sheep in northern Kenya using an Ehrlichia ruminantium polyclonal competitive ELISA - Collins, M.; Ngetich, Collins; Owido, Milton; Getange, D.; Harris, R.; Bargul, J.L.; Bodha, B.; Njoroge, D.; Muloi, Dishon M.; Martins, D.J.; Villinger, J.; Githaka, Naftaly W.; et al. (MDPI, 2022)
A disease with clinical and post-mortem presentation similar to those seen in heartwater, a tick-borne disease of domestic and wild ruminants caused by the intracellular bacterium Ehrlichia ruminantium, was first reported in dromedary camels in Kenya in 2016; investigations carried out at the time to determine the cause were inconclusive. In the present study, we screened sera from Kenyan camels collected before (2015) and after (2020) the 2016 disease outbreak for antibodies to Ehrlichia spp. using an E. ruminantium polyclonal competitive ELISA (PC-ELISA). Median antibody levels were significantly higher (p < 0.0001) amongst camels originating from areas where the heartwater-like disease was reported than from disease-free areas, for animals sampled in both 2015 and 2020. Overall median seropositivity was higher in camels sampled in 2015 than in 2020, which could have been due to higher mean age in the former group. Camels that were PCR-positive for Candidatus Ehrlichia regneryi had significantly lower (p = 0.03) median antibody levels than PCR-negative camels. Our results indicate that Kenyan camels are frequently exposed to E. ruminantium from an early age, E. ruminantium was unlikely to have been the sole cause of the outbreak of heartwater-like disease; and Ca. E. regneryi does not appreciably cross-react with E. ruminantium in the PC-ELISA.